Performance Evaluation of Seawater-Mixed Mortar under Carbonation Exposure for Sustainable Repair Applications - Pinta Astuti; Adinda Dewi Puspitasari; Ahmad Choiry Fajar; Anisa Zulkarnain; Adhitya Yoga Purnama (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Corrosion and carbonation pose significant risks to reinforced concrete structures, necessitating timely patch repairs, especially when using seawater-mixed mortar. This study evaluated the influence of binder type, cover thickness, corrosion protection methods, and exposure conditions on the durability of reinforced concrete. Specimens using Portland Pozzolan Cement (PPC) and Portland Composite Cement (PCC) with 3 cm and 5 cm cover depths were tested over 400 days. PCC exhibited superior corrosion resistance due to its higher CaO content, enhancing strength, reducing permeability, and limiting chloride ion ingress. Surface concrete coatings were the most effective in mitigating carbonation, limiting carbonation depth to 0.38 cm, while steel-coated and uncoated specimens showed greater depths of 0.50 cm and 0.55 cm, respectively. Exposure conditions significantly influenced performance, with dry and dry-wet cycles accelerating carbonation, while wet conditions provided better protection. The findings recommend PCC-based mortar combined with surface coatings for patch repair applications to improve long-term durability in marine environments.